2013
DOI: 10.1177/0894845313481851
|View full text |Cite
|
Sign up to set email alerts
|

Key Relationships for International Student University-to-Work Transitions

Abstract: International student research predominantly focuses on the initial and middle stages of their sojourn. Our research, however, specifically addresses how relationships support international students to successfully navigate the late-stage transition from university to work. In this qualitative study, we interviewed 18 international students from diverse cultures, ages, and professions with an emphasis on their last year of university and 3 years post-graduation. We found six major themes: (a) building strong f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 36 publications
1
31
0
2
Order By: Relevance
“…As Popadiuk and Arthur (2014) argue research centred on international students tends to concentrate on initial and middle stages of their sojourn, with limited consideration of support given to international students support them through the transition from university to work.…”
Section: Discussionmentioning
confidence: 99%
“…As Popadiuk and Arthur (2014) argue research centred on international students tends to concentrate on initial and middle stages of their sojourn, with limited consideration of support given to international students support them through the transition from university to work.…”
Section: Discussionmentioning
confidence: 99%
“…Networking has particular benefits for international students. In a qualitative study of international students in Canada, most of whom were originally from Asian countries, Popadiuk and Arthur () found that relationships within the host country were crucial in assisting students' transition from university to work. Additionally, relationship building and networking resulted in opportunities for referrals to employers and contacts that assisted in career decision making.…”
Section: Challenges For Korean International Studentsmentioning
confidence: 99%
“…Additionally, relationship building and networking resulted in opportunities for referrals to employers and contacts that assisted in career decision making. Relationships that facilitate career networking provide international students with essential information, such as an understanding of cultural nuances in the job‐search process (Popadiuk & Arthur, ).…”
Section: Challenges For Korean International Studentsmentioning
confidence: 99%
“…Although research has substantiated the point that most international students pursue international education due to perceived career opportunities in the future (Arthur & Flynn, 2011Brooks, Waters, & Pimlott-Wilson, 2012;Masumba, Jin, & Mjelde, 2011), the current study focuses on the actual experiences of international students who pursued employment in the destination country. There are few studies that account for how international students successfully navigate the transition to employment in the destination country, how they overcome barriers, and what helps them to integrate into local employment and community contexts (Popadiuk & Arthur, 2013;Sangganjanavanich, Lenz, & Cavazos, 2011). The current study focused on international students' perceived barriers and what they identified as facilitators of their career transition.…”
Section: Positioning the Current Studymentioning
confidence: 99%